High-temperature study of octahedral cation exchange in olivine by neutron powder diffraction - Henderson, C; Knight, K; Redfern, S; Wood, B (1996)
Time-of-flight, neutron powder diffraction to 1000°C provides precise octahedral site occupancies and intersite distribution coefficients for MnMgSiO4 and MnFeSiO4 olivines. Intersite exchange occurs in minutes down to 500°C. Equilibrium distribution coefficients show that manganese ordering into the larger octahedral site decreases with increasing temperature. Exchange energies are 15.7 and 10.1 kilojoules per mole for magnesium-manganese and iron-manganese, respectively. Distribution coefficients deduced for FeMgSiO4 olivine suggest an exchange energy of 4.8 kilojoules per mole. Intersite exchange energies are consistent with diffusion coefficients in the order iron > magnesium > manganese. Geothermometry based on magnesium-manganese and iron-manganese exchange may be possible only for samples equilibrated below 500°C.